HUBUNGAN KONSEP DIRI DENGAN PERILAKU BERPAKAIAN PADA PENGGEMAR K-POP DAN K-DRAMA (HALLYU WAVE) - Eka, Eka Syafitri; Rasmanah, Manah; Janare Putra, Bela (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2024)
The study is entitled "The Relationship of Self-Concept with Dressed Behavior in K-Pop and K-Drama Fans (Hallyu Wave). The aim of the study is to find out the relationship between self-concept and dressed behavior among K-pop and K -drama fans. This type of research is quantitative with correlation methods. The sample was taken from a total of 30 students using purposesive sampling techniques, where the criteria are K-pop and K-drama (hallyu wave) students, focusing on female students, students who access K-Pop and K -drama with intensity frequently and very often. Data collection techniques using questionnaires or queries and documentation, with a total of about 20 questions from each variable. Once validity tested with R count result greater than R table then the instrument is declared valid. Data analysis techniques used using moment product correlation tests. The results of this study show that from the product moment correlation data test results there is a relationship between self-concept and dressed behavior with a strong relationship category. The determination of the relationship is based on the interpretation of a coefficient of 0.60-0.799. The two variables have a positive relationship, which means that the more self-concepts are overwhelmed, the more K-pop and K-drama fans dress up. (hallyu wave).